2018
DOI: 10.1016/j.cmet.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

A Role for p53 in the Adaptation to Glutamine Starvation through the Expression of SLC1A3

Abstract: SummaryNumerous mechanisms to support cells under conditions of transient nutrient starvation have been described. Several functions of the tumor-suppressor protein p53 can contribute to the adaptation of cells to metabolic stress and help cancer cell survival under nutrient-limiting conditions. We show here that p53 promotes the expression of SLC1A3, an aspartate/glutamate transporter that allows the utilization of aspartate to support cells in the absence of extracellular glutamine. Under glutamine deprivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
152
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(156 citation statements)
references
References 49 publications
4
152
0
Order By: Relevance
“…GLS deficiency, in contrast, allows glutamine uptake but leads to both glutamate and aspartate deficiencies and increased ROS. Glutamate and glutamine can be generated from other sources, such as aspartate, which can be p53 dependent and induce cell survival in glutamine-limiting conditions (Tajan et al, 2018). Given the interconnections of each metabolite in these pathways, it is likely that inhibition of this metabolic network leads to context-specific outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…GLS deficiency, in contrast, allows glutamine uptake but leads to both glutamate and aspartate deficiencies and increased ROS. Glutamate and glutamine can be generated from other sources, such as aspartate, which can be p53 dependent and induce cell survival in glutamine-limiting conditions (Tajan et al, 2018). Given the interconnections of each metabolite in these pathways, it is likely that inhibition of this metabolic network leads to context-specific outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, we observed that SLC1A3 expression could promote cancer cell metastasis, regardless of asparagine bioavailability (Figs D and EV5E). Even though recent studies mainly focused on the role of SLC1A3 in mediation of aspartate uptake (Alkan et al , ; Garcia‐Bermudez et al , ; Sullivan et al , ; Tajan et al , ), we could not exclude the role of glutamate, which could be converted to aspartate via oxidative or reductive carboxylation. This is supported by our findings that both aspartate and glutamate could rescue ASNase toxicity in SLC1A3 KO or negative cancer cells (Figs H and I).…”
Section: Discussionmentioning
confidence: 94%
“…SLC1A3 is mainly expressed in brain tissues (Fig EV1C), critical for the termination of excitatory neurotransmission (Kanai et al , ). Recent studies have highlighted the importance of SLC1A3‐mediated aspartate uptake for cancer cell proliferation under hypoxia and crosstalk between cancer cells and cancer‐associated fibroblasts in the tumor niche (Alkan et al , ; Garcia‐Bermudez et al , ; Sullivan et al , ; Tajan et al , ; Bertero et al , ). We also observed elevated SLC1A3 RNA levels in several tumor types from the TCGA database [especially kidney renal clear cell carcinoma (KIRC, P = 5.5 × 10 −30 ), kidney renal papillary cell carcinoma (KIRP, P = 2.1 × 10 −10 ), liver hepatocellular carcinoma (LIHC, P = 3.2 × 10 −10 ), and stomach adenocarcinoma (STAD, P = 6.1 × 10 −5 )] (Fig EV1D).…”
Section: Resultsmentioning
confidence: 99%
“…Similar processes are likely to occur in other cancers. Indeed, recently EAAT1 has been implicated in supporting proliferation in several cancer cell lines representing solid cancers [62,63]. Both studies showed a main role for EAAT1 in the uptake of aspartate from the medium, especially under conditions of glutamine deprivation or asparaginase treatment.…”
Section: Discussionmentioning
confidence: 99%